DARI RELIEF CANDI MENUJU KARYA TARI: SEBUAH CATATAN KREATIF - Anggono Kusumo Wibowo (Institut Seni Indonesia Surakarta, 2013)
Temple reliefs appear to store data about motifs portraying dance movements that wereknown in the past, although in their depiction, these movements appear broken or fragmented(nyeklèk). As an analogy to this, the pattern of nyeklèkan movements that are well-known inthe Cakil dance can provide a source for creative ideas in the creation of new dances. The questionto be addressed in this paper is how we can use the temple reliefs as a source for creative ideas innew dances. The method used was to trace the values found on temple reliefs and then apply themto the context of performing dance movements, as well as in relation to kinesiology and thesegmentation of the body. Although not in a literal sense, this paper aims to discover the meaningof nyeklèk in all aspects of a performance (movement, music, and artistic setting). In this way,temple reliefs can be understood as the product of a traditional work in the form of artefacts thatcontain a particular meaning. Tradition apparently remains an endless source of ideas. Nyeklèkan,which until now has been understood as a vertex and or a defined bending of the body in Cakilanand strong male dance, is explored in refined or alusan dance with its free flowing movements byadapting the techniques of flowing contemporary dance movements which are based on the techniqueof releasing movements. Nyeklèkan is seemingly a moving frame of movements that areperformed with a technique of freezing at certain points. This provides a rich artistic contrastwhich shows the freedom and ability of the body to perform (or express the language of) a highquality of movements, in every segment of the body, in every field of stance, and in every techniquewhich is applied (whether traditional Javanese or modern-contemporary dance).